Analisis Kompetensi Pedagogical Content Knowledge Calon Guru Fisika Berdasarkan Instrumen CoRe dan PaP-eRs Pada Materi Gelombang Bunyi - Mulhayatiah, Diah; Agnia, L Syifa; Suhendi, H Y (Universitas PGRI Semarang, 2021)
PCK competencies are one of the important competencies for prospective physics teachers to have. The measurement of PCK competence for prospective physics teachers can be done using two instruments developed by Loughran, namely the CoRe and PaP-eRs instruments. This study aims to determine and describe the PCK competencies of prospective physics teachers in sound wave metering based on the CoRe instrument, the learning process and PaP-eRs. The method used in this research is descriptive qualitative and carried out by researchers as prospective physics teachers who teach second semester students of physics education study program UIN Sunan Gunung Djati Bandung. The results showed that the PCK competency of prospective teachers based on the CoRe instrument was in the Maturing PCK category or level 3 with a score of 88.17. The PCK competence of prospective teachers based on the learning process is in the effective category with a percentage of 77.67% and based on the PaP-eRs instrument, the PCK competencies of prospective teachers are in the Maturing PCK category or level 3 with a score of 85.18.Â Keywords: PCK, CoRe, PaP-eRs